A long way from Chicago : a novel in stories - Peck, Richard, 1934- (New York : Puffin, 2000)
A boy recounts his annual summer trips to rural Illinois with his sister during the Great Depression to visit their larger-than-life grandmother.
A National Book. Award Finalist
Keywords: Grandmothers -- Fiction; Country life -- Fiction